Mapping the Knowledge Domain of Earnings Conference Calls: A Bibliometric Study - Zhang, Changye; Chen, Fang; Liao, Jinhao; Wang, Anyue (Technium Social Sciences Journal, 2025)
This study uses a bibliometric approach to conduct a critical review of research on earnings conference calls. The goal of the study is to assess the development of the field, identify key research trends and issues, and highlight gaps in the existing literature. This study takes the Web of Science (WOS) academic journal database as the source of literature. It utilizes software such as COOC, DIKW, VOSviewer, and Vismap for bibliometric analysis, mathematical statistics, and knowledge graph drawing. The study constructs knowledge graphs for the research field of earnings conference calls from 2000 to 2025. It covers aspects such as publication volume, research institutions, authors, and keywords, and deeply analyzes their distribution patterns and evolutionary trends to comprehensively trace the research trajectory of this field. The results show that: (1) the publication volume in the field of earnings conference calls presents a linear, year-by-year increase in research papers in this field, indicating that the research on earnings conference calls is in a stage of rapid development. (2) The cooperation intensity among authors is robust, extensive, and tightly knit, indicating the formation of a well-developed collaborative network. In the research field of earnings conference calls, the USA, China, and Canada are the top three contributing countries, with the USA accounting for nearly half of the contributions. (3) Co-occurrence analysis of these keywords reveals a close relationship among them, indicating strong thematic connections within the research domain. (4) The evolution of keywords reveals a notable shift in scholarly focus from traditional economic perspectives to more interdisciplinary approaches, incorporating linguistic and machine-learning perspectives. This trend reflects an increasing emphasis on analyzing financial phenomena through diverse disciplinary lenses. This study underscores the need for more focused research in these perspectives, offering important implications for sustainable earnings conference calls release management. It also underscores the potential for collaborative opportunities within academia to better understand future trends.